Cloning of cytadhesin protein gene (pvpA) and expression analysis of recombinant fusion protein of Mycoplasma gallisepticum - MANIMARAN, K; MISHRA, ADARSH; HARINI, V; SHIVACHANDRA, SATHISH B; MEENAMBIGAI, T V; RAJ, G DHINAKAR (The Indian Journal of Animal Sciences, 2021)
Chronic respiratory disease (CRD) caused by Mycoplasma gallisepticum (MG) is one of the major respiratory tract infections of the poultry, resulting in significant economic loss to the poultry farmers. Diagnosis of such ailment is highly necessary for effective control measures. In addition, promising molecular tools are warranted for efficient epidemiological tracing of the outbreaks. The study was focused on the elucidation of phase variable cytadhesin protein gene (pvpA) of MG through cloning and expression analysis. A set of primers targeting the pvpA gene of MG was designed. The complete pvpA gene was amplified and cloned into pUC-derived expression vector pRSETA. Finally, the recombinant clones were examined through colony PCR and restriction endonuclease (RE) analysis with EcoR1 and BamH1 enzymes followed by sequencing. The expression of the recombinant pvpA gene was optimized at 1.4mM/Î¼l concentration of Isopropyl-β-D-thiogalactoside induction at 30Â°C. The recombinant fusion protein was purified by immobilized metal affinity chromatography and characterized by SDS-PAGE followed by confirmation of recombinant cytadhesin fusion protein through western blot analysis. The pvpA gene was successfully cloned and expressed. The deduced amino acid sequence analysis had shown the presence of two direct repeats (DR1 and DR2) along with predicted PRP motifs repeatedly with high proline encoding regions at the carboxy-terminal of pvpA gene indicating its scope for epidemiological studies.